Complementary Therapy and Holistic Nursing Care Plan - Haryanti, Dwi Yunita; Rahman, Sabila Aulia (Universitas Muhammadiyah Jember, 2024)
Complementary therapy regulated fundamental caring principles and integrated as part of nursing care management. Nursing concept model of caring for patients widely opens a chance to encourage individual abilities as a nurse in modifying holistic nursing care plans and also improving nurse-patient relationships. The aim of this study was to determine nursing student's knowledge and the use of complementary therapy in holistic nursing care plans. A descriptive cross sectional survey was performed among nursing students in the Faculty of Health Science who had established nursing care plan and was in final year of education. Participants taken by total sampling (n=115). Questionnaire completed with participants to determine their knowledge, personal methods use and reasons toward complementary therapy. The participants had a good knowledge towards complementary therapy. More than a half of the participants reported that they use of relaxation therapy, herbs, cupping therapy and Qur'an recitation into their nursing care plan so that patients can be treated as a holistic from the side of patients biology, psychology, sociology and spiritualism needs. Nursing students engaged complementary therapy in their nursing care plan. Good knowledge about complementary therapies in nursing students will increase the use of these therapies in providing nursing care. Nurses with the caring concept model are in a strategic position to be able to provide holistic nursing care, one of which is by implementing complementary therapies in the nursing plan.